Citra Objek Wisata Kampung Lawas Maspati, Kota Surabaya di Mata Wisatawan Nusantara - Tiara Wardani (Program Studi Pariwisata Fakultas Ilmu Budaya Universitas Gadjah Mada Yogyakarta, 2019)
This study aimed to determine the image of Kampung Lawas Maspati as perceived by domestic tourists and how to improve the image. Kampung Lawas Maspati is known as a kampong tourist attraction in Surabaya that has the community’s local historical value and wisdom as its attraction. This research used quantitative and qualitative data. The data collected through questionnaires distributed to 92 respondents. Besides, interviews were employed with the organiser of tourist attraction and visitors. The result showed that Kampung Lawas Maspati has an excellent image as perceived by the domestic tourist, for the cognitive and affective component, also the overall image. Therefore, the efforts to improve the image by improving each component and creating innovation for tourist activity.